Mengapa dan bagaimana saya marah? Studi eksplorasi mengenai penyebab dan pilihan ekspresi marah pada remaja Islam beretnis Sunda - F Fridayanti; Elis Anisah Fitriah (Jurnal Psikologi Ulayat, 2021)
This study aimed to explore how the Islamic Sundanese adolescents experience and express their anger. A total of 697 students from two high school in Bandung and Tasikmalaya participated in the survey. Data was qualitatively collected using a questionnaire that recorded the causes and expressions of the participants’ anger. The obtained data was analyzed using content analysis. The findings suggest three emerging themes regarding the causes of anger among the Sundanese adolescents: 1) related to disturbing situations, 2) related to people (attitudes, behaviors and personal characteristics), and 3) related to other things (mood, feelings of depression, and physiological conditions). Participants mostly expressed their anger through passive and non-verbal expressions. Their reactions towards anger appeared to be associated with their Islamic religious values (which most participants were affiliated with), such as taking wudhu, istigfhar, pray, be patient and sincere, as well as perform sholat.